Implementasi Pendidikan Karakter Terintegrasi Nilai Kearifan Lokal di Madrasah Aliyah - Muhaemin Muhaemin; Henri Henri (IQRO: Journal of Islamic Education, 2022)
This study aims to analyze efforts to optimize character education; to formulate steps to integrate local wisdom values into character education; and to map out solutions for optimizing character education based on local wisdom, especially for students at the MAN Palopo. The type of research used in this research is descriptive qualitative, with the subject of research MAN Palopo teachers, the data source used is primary data and secondary data, with data collection techniques through observation, interviews, and documentation. The results of the study found that the implementation of character education for students at MAN Palopo included; integrating the values of local wisdom in the learning process at the MAN Palopo which includes sipakatau, sipakalebbi, sipakangie. As for the solution to optimizing character education based on local wisdom at MAN Palopo, there are 2 things that are being done by the madrasa as a solution to optimizing character education, including; Collaborate with teachers and parents of students and hold additional activities such as extracurricular activities (scout, paskib, and PMR) and create additional classes, namely the tahfidz class and research class.